Effectiveness of the Oral Human Attenuated Rotavirus Vaccine: A Systematic Review and Meta-analysis—2006–2016. (12th November 2018) - Willame, Corinne; Vonk Noordegraaf-Schouten, Marije; Gvozdenović, Emilia; Kochems, Katrin; Oordt-Speets, Anouk; Praet, Nicolas; van Hoorn, Rosa; Rosillon, Dominique
Abstract: Background: Gastroenteritis caused by rotavirus accounts for considerable morbidity in young children. We aimed to assess the vaccine effectiveness (VE) of the oral rotavirus vaccine Rotarix, as measured by laboratory-confirmed rotavirus infection after referral to hospital and/or emergency departments in children aged <5 years with gastroenteritis. Methods: We performed a systematic search for peer-reviewed studies conducted in real-life settings published between 2006 and 2016 and a meta-analysis to calculate the overall Rotarix VE, which was further discriminated through stratified analyses. Results: The overall VE estimate was 69% (95% confidence interval [CI], 62% to 75%); stratified analyses revealed a non-negligible impact of factors such as study design and socioeconomic status. Depending on the control group, VE ranged from 63% (95% CI, 52% to 72%) to 81% (95% CI, 69% to 88%) for unmatched and matched rotavirus test–negative controls. VE varied with socioeconomic status: 81% (95% CI, 74% to 86%) in high-income countries, 54% (95% CI, 39% to 65%) in upper-middle-income countries, and 63% (95% CI, 50% to 72%) in lower-middle-income countries. Age, rotavirus strain, and disease severity were also shown to impact VE, but to a lesser extent. Conclusions: This meta-analysis of real-world studies showed that Rotarix is effective in helping to prevent hospitalizations and/or emergency department visits due to rotavirus infection.